Evolutionary History of Copper Membrane Monooxygenases - Khadka, Roshan; Clothier, Lindsay; Wang, Lin; Lim, Chee Kent; Klotz, Martin G.; Dunfield, Peter F. (Frontiers in Microbiology, 2018)
Copper membrane monooxygenases (CuMMOs) oxidize ammonia, methane and some short-chain alkanes and alkenes. They are encoded by three genes, usually in an operon of xmoCAB. We aligned xmo operons from 66 microbial genomes, including members of the Alpha-, Beta-, and Gammaproteobacteria, Verrucomicrobia, Actinobacteria, Thaumarchaeota and the candidate phylum NC10. Phylogenetic and compositional analyses were used to reconstruct the evolutionary history of the enzyme and detect potential lateral gene transfer (LGT) events. The phylogenetic analyses showed at least 10 clusters corresponding to a combination of substrate specificity and bacterial taxonomy, but with no overriding structuring based on either function or taxonomy alone. Adaptation of the enzyme to preferentially oxidise either ammonia or methane has occurred more than once. Individual phylogenies of all three genes, xmoA, xmoB and xmoC, closely matched, indicating that this operon evolved or was consistently transferred as a unit, with the possible exception of the methane monooxygenase operons in Verrucomicrobia, where the pmoB gene has a distinct phylogeny from pmoA and pmoC. Compositional analyses indicated that some clusters of xmoCAB operons (for example, the pmoCAB in gammaproteobacterial methanotrophs and the amoCAB in betaproteobacterial nitrifiers) were compositionally very different from their genomes, possibly indicating recent lateral transfer of these operons. The combined phylogenetic and compositional analyses support the hypothesis that an ancestor of the nitrifying bacterium Nitrosococcus was the donor of methane monooxygenase (pMMO) to both the alphaproteobacterial and gammaproteobacterial methanotrophs, but that before this event the gammaproteobacterial methanotrophs originally possessed another CuMMO (Pxm), which has since been lost in many species.